The Influence of Work Life Balance and Flexible Work Arrangement on Employee Performance with Satisfaction as a Mediation (Case Study of Compassion Indonesia Employees) - Difi Alfa Wijayana Murdowo; R Tri Priyono Budi Santoso; Yeyen Komalasari; Gilbert Nainggolan (The Eastasouth Management and Business, 2026)
This study aims to explain the influence of Work Life Balance (WLB) and Flexible Work Arrangement (FWA) on employee performance with job satisfaction as a mediating variable in Compassion Indonesia employees. This study uses a quantitative approach with a cross-sectional survey design. The sample was taken was 141 employees from Compassion Indonesia. The data collection method in this study was a questionnaire with a Likert scale. The analysis techniques used were descriptive analysis, validity test, reality test, composite reliability, average variance extracted (AVE), R test, and f test. Based on the hypothesis test, the result obtained were that job satisfaction, Work Life Balance (WLB) and Flexible Work Arrangement (FWA) have a positive and significant effect on the performance of Compassion Indonesia employees. The suggestion for future research is to develop further studies to identify the factors that encourage employees to improve performance.